2013
DOI: 10.1121/1.4796129
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the production rate of biosonar signals in freshwater porpoises

Abstract: The biosonar (click train) production rate of ten Yangtze finless porpoises and their behavior were examined using animal-borne data loggers. The sound production rate varied from 0 to 290 click trains per 10-min time interval. Large individual differences were observed, regardless of body size. Taken together, however, sound production did not differ significantly between daytime and nighttime. Over the 172.5 h of analyzed recordings, an average of 99.0% of the click trains were produced within intervals of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…These findings suggest that porpoises are primarily engaged in crepuscular and nocturnal foraging in the port area. Considering that no significant diel patterns were observed in the frequency and duration of porpoise echolocation encounters, the diel pattern of porpoise acoustic behavior appears to be due to porpoises producing more click trains and buzzes at night [39] and possibly in the evening. These findings are consistent with findings from previous studies that show no reduced nocturnal activity among Yangtze finless porpoises in captivity [6].…”
Section: Discussionmentioning
confidence: 78%
“…These findings suggest that porpoises are primarily engaged in crepuscular and nocturnal foraging in the port area. Considering that no significant diel patterns were observed in the frequency and duration of porpoise echolocation encounters, the diel pattern of porpoise acoustic behavior appears to be due to porpoises producing more click trains and buzzes at night [39] and possibly in the evening. These findings are consistent with findings from previous studies that show no reduced nocturnal activity among Yangtze finless porpoises in captivity [6].…”
Section: Discussionmentioning
confidence: 78%
“…The vocalizations from several dozen individual humpback dolphins were probably recorded in the current study; however, it is not possible to verify this estimate, because individual identification from echolocation click trains has not been conducted to date. Biologging studies of other dolphins or porpoises have shown large differences among individuals in the production of signals and behaviour (Kimura et al, 2013;Rasmussen et al, 2013). Furthermore, the ecology and acoustic behaviour of humpback dolphin individuals might differ across regions, because they have patchy distributions (Jefferson & Hung, 2004) and strong site fidelity (Xu et al, 2012), even in Chinese waters.…”
Section: Discussionmentioning
confidence: 99%
“…Even if fishers generally do not intend to catch or harm porpoises on purpose (Turvey et al, ), unintentional injuries to porpoises may result from the animals becoming entangled or interacting with gear underwater. Yangtze finless porpoises have been shown to be primarily nocturnal and crepuscular feeders, and are more active during the night and at dawn (Akamatsu, Wang, Wang, Li, & Dong, ; Kimura et al, ; Wang, Akamatsu, Wang, & Wang, ). The potential temporal overlap between the porpoise foraging time and the illegal fishing time may therefore lead to a higher risk of collateral damage to porpoises (Jefferson & Curry, ).…”
Section: Discussionmentioning
confidence: 99%